The conservation of number and location of 18S sites indicates the relative stability of rDNA in species of Pentatomomorpha (Heteroptera) - Bardella, Vanessa Bellini [UNESP]; Fernandes, Thiago; Laforga Vanzela, Andre Luis (Canadian Science Publishing, Nrc Research Press, 2013)
Fluorescent in situ hybridization (FISH) with rDNA probes has been used for comparative cytogenetics studies in different groups of organisms. Although heteropterans are a large suborder within Hemiptera, studies using rDNA are limited to the infraorder Cimicomorpha, in which rDNA sites are present in the autosomes or sex chromosomes. We isolated and sequenced a conserved 18S rDNA region of Antiteuchus tripterus (Pentatomidae) and used it as a probe against chromosomes of 25 species belonging to five different families of Pentatomomorpha. The clone pAt05, with a length of 736 bp, exhibited a conserved stretch of 590 bp. FISH analysis with the probe pAt05 always demonstrated hybridization signals in sub-terminal positions, except for Euschistus heros. Apparently, there is a tendency for 18S rDNA sites to locate in autosomes, except for Leptoglossus gonagra and Euryophthalmus rufipennis, which showed signals in the m-and sex chromosomes, respectively. Although FISH has produced evidence that rearrangements are involved in rDNA repositioning, whether in different autosomes or between sex and m-chromosomes, we have no conclusive evidence of what were the pathways of these rearrangements based on the evolutionary history of the species studied here. Nevertheless, the diversity in the number of species analyzed here showed a tendency of 18S rDNA to remain among the autosomes.
Keywords: chromosome heteromorphism; Holocentric chromosomes; in situ hybridization; 45S rDNA; m-chromosomes